A Comparison of Removal Rates of Headless Screws Versus Headed Screws in Calcaneal Osteotomy. Issue 5 (October 2018) - Kunzler, Daniel; Shazadeh Safavi, Pejma; Jupiter, Daniel; Panchbhavi, Vinod K.
Background: Calcaneal osteotomy has been used to successfully treat both valgus and varus hindfoot deformities. Pain associated with implanted hardware may lead to further surgical intervention for hardware removal. Headless screws have been used to reduce postoperative hardware-associated pain and accompanying hardware removal, but data proving their effectiveness in this regard is lacking. The purpose of this study is to compare the rates of removal of headed and headless screws utilized in calcaneal osteotomy. Methods: We conducted a retrospective chart review of 74 patients who underwent calcaneal osteotomy between January 2010 and December 2014. The cohort was divided into 2 groups by fixation method: a headed screw and a headless screw group. Bivariate associations between infection or hardware removal, and screw type, screw head width, gender, smoking status, alcohol, hypertension, diabetes, hyperlipidemia, age, and body mass index were assessed using t-tests and Fisher's exact/χ 2 tests for continuous and discrete variables, respectively. Results: Headed screws were removed more frequently than headless screws (P < .0001): 15 of 30 (50%) feet that received headed screws and 4 of 44 (9%) of feet that received headless screws underwent subsequent revision for screw removal. In all cases, screws were removed because of pain. The calcaneal union rate was 100% in both cohorts. Conclusion: The rate of screw removal in calcaneal osteotomies is significantly lower in patients who receive headless screws than in those receiving headed screws. Levels of Evidence: Level IV